Persepsi Petani terhadap Pengaruh Faktor Internal dalam Sistem Peremajaan Kelapa Sawit Model Tumbang Serempak Berkelanjutan di Kecamatan Muara Papalik Kabupaten Tanjung Jabung Barat - Ja’afar, Ja’afar; Suandi, Suandi; Rosyani, Rosyani (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the perception of oil palm farmers regarding the sustainable simultaneous fall rejuvenation system. Knowing and analyzing the rejuvenation system of the sustainable simultaneous fall model with the perceptions of oil palm farmers in Muara Papalik District, West Tanjung Jabung Regency. The research model uses observation, surveys, interviews and distributing questionnaires to farmers in Intan Jaya Village and Sungai Papauh Village from September to November 2023. The research instrument uses a Likert Scale as an indicator that can be measured. The close relationship between aspects that influence farmers' perceptions with the Spearman Rank Correlation test using the SPSS application. The research results show that the perception of the input aspect has a positive value of 83.78%; financial aspect 78.37%; market aspect 82.43%; technological aspects 78.38%; institutional aspect 79.72% and income aspect 82.44%. Meanwhile, the ecological aspect in implementing oil palm rejuvenation using a sustainable simultaneous fall model needs to be a sustainable socio-economic study. The perception-forming aspect has a strong relationship with the input aspect, financial aspect, market aspect, technological aspect and income aspect, while the institutional aspect is weak. Farmers' perceptions of the sustainable simultaneous fall rejuvenation model from six aspects have a close influence on oil palm rejuvenation.